Varieties of spoken French - Durand, Jacques 1947-; Laks, Bernard; Lyche, Chantal (Oxford linguistics, 2016)
This book examines the variation found in modern spoken French, based on the research programme 'Phonology of Contemporary French' (Phonologie du Français Contemporain, PFC). Extensive data are drawn from all over the French-speaking world, including Algeria, Canada, Louisiana, Mauritius, and Switzerland.